Hepatitis B virus sensitivity to interferon‐α in hepatocytes is more associated with cellular interferon response than with viral genotype. Issue 4 (22nd February 2018) - Shen, Fang; Li, Yaming; Wang, Yang; Sozzi, Vitina; Revill, Peter A.; Liu, Jiangxia; Gao, Lu; Yang, Guang; Lu, Mengji; Sutter, Kathrin; Dittmer, Ulf; Chen, Jieliang; et al.
Abstract : Interferon‐α (IFN‐α) is used to treat chronic hepatitis B virus (HBV) infection, but only 20%‐40% of patients respond well. Clinical observations have suggested that HBV genotype is associated with the response to IFN therapy; however, its role in viral responsiveness to IFN in HBV‐infected hepatocytes remains unclear. Here, we produced infectious virions of HBV genotypes A to D to infect three well‐recognized cell–culture–based HBV infection systems, including primary human hepatocytes (PHH), differentiated HepaRG (dHepaRG), and HepG2‐NTCP cells to quantitatively compare the antiviral effect of IFN‐α on HBV across genotypes and cell models. The efficacy of IFN‐α against HBV in hepatocytes was generally similar across genotypes A2, B5, C2, and D3; however, it was significantly different among the infection models given that the half maximal inhibitory concentration value of IFN‐α for inhibition of viral DNA replication in PHH (<20 U/mL) and dHepaRG cells were much lower than that in HepG2‐NTCP cells (>500 U/mL). Notably, even in PHH, IFN‐α did not reduce HBV covalently closed circular DNA at the concentrations for which viral antigens and DNA replication intermediates were strongly reduced. The three cell‐culture models exhibited differential cellular response to IFN‐α. The genes reported to be associated with responsiveness to IFN‐α in patients were robustly induced in PHH while weakly induced in HepG2‐NTCP cells upon IFN‐α treatment. Reduction or promotion of IFN response in PHH or HepG2‐NTCP cells significantly attenuated or improved the inhibitory capacity of IFN‐α on HBV replication, respectively. Conclusion: In the cell–culture–based HBV infection models, the sensitivity of HBV to IFN‐α in hepatocytes is determined more by the cell‐intrinsic IFN response than by viral genotype, and improvement of the IFN response in HepG2‐NTCP cells promotes the efficacy of IFN‐α against HBV. (Hepatology 2018;67:1237‐1252).